Réponses

2013-02-09T21:01:25+01:00

a) (√3 + √5)²

= (√3)² (√5)² + 2(√3)(√5)

= 3 + 5 + 2√15

= 8 + 2√15

 

* a² + b² + 2(a)(b)

 

b) (√3-√5)(√3+√5)

= (√3)² - (√5)²

= 3 - 5

= -2

 

* a² - b²

 

c) (√5-√3)²

= (√5)² + (√3)² - 2(v5)(√3)

= 5 + 3 - 2√15

= 8 - 2√15

 

d) (√5-√3)(√5+√3)

= (√5)² - (√3)²

= 5 - 3

= 2

 

Ce sont les même calculs mais juste les signes qui changent, je t'ai tout détaillé.

2013-02-09T21:05:24+01:00

 (√3 + √5)²

= √3² + √5²

= 3 + 5= 

* a² + b² + 2(a)(b)

 

b) (√3-√5)(√3+√5)

= (√3)² - (√5)²

= 3 - 5

-2

 

* a² - b²

 

c) (√5-√3)²

= (√5)² + (√3)² - 2(v5)(√3)

= 5 + 3 - 2√15

8 - 2√15

 

d) (√5-√3)(√5+√3)

= (√5)² - (√3)²

= 5 - 3

2